The Role of Context in Semantic Interpretation: Analyzing Ambiguity and Polysemy in English Discourse - Salsa Sabilla Alin Safitri; Nargis; Asep Suhendar (Universitas Islam Negeri Palopo, 2026)
This research investigates the role of context in the semantic interpretation of ambiguity and polysemy in English news discourse. Using a qualitative descriptive approach and content analysis method, the study examines four selected news articles from BBC News and NBC News. The analysis identifies four main categories of ambiguity: contextual, type, relationship meaning, and source ambiguity. The most dominant type is contextual ambiguity, which often arises due to insufficient background information or vague expressions. The findings highlight how ambiguity and polysemy can hinder accurate interpretation and impact public understanding. Context proves crucial in determining meaning, especially in complex or sensitive news topics such as gender, crime, and environmental issues. This study emphasizes the need for media to present information transparently and for readers to be critically aware of linguistic nuances. The findings also contribute to improving communication effectiveness in translation, cross-cultural understanding, and natural language processing.